HAKIKAT KONTRAK MENURUT ROSCOE POUND DAN RELEVANSINYA TERHADAP KONTRAK YANG BERKAITAN DENGAN LINGKUNGAN HIDUP - FIRMANDA S, HENGKI (Jurnal Yuridis, 2016)
The contract is forming reality that can be affect the parties as the subject of the contract and the environment as the object of the contract. Contracts create a new reality from reality than ever before. The realization of the contract in the precontractual will be different from the reality in the post contractual contract. Pound explained that the contract is a promise made by the parties. The contract is meant by Pound are private contract. Although the contract is private, essence the contract must promote a balance in performing the contract. The need for balance because humans are confronted by free will with the will to obey his word. Pound said in keeping promises to the fulfillment of the contract was part of a social community interest. Contracts relating to the environment as the object of the contract must be in balanced position. The balanced in treating the object of the contract, so that the environment is not incorporated by satisfying human needs, but as the fulfillment of human balance at the time of human life.